2023
DOI: 10.1130/g50641.1
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope and biostratigraphic evidence for an expanded Paleocene–Eocene Thermal Maximum sedimentary record in the deep Gulf of Mexico

Abstract: In this study, we present evidence of a Paleocene–Eocene Thermal Maximum (PETM) record within a 543-m-thick (1780 ft) deep-marine section in the Gulf of Mexico (GoM) using organic carbon stable isotopes and biostratigraphic constraints. We suggest that climate and tectonic perturbations in the upstream North American catchments can induce a substantial response in the downstream sectors of the Gulf Coastal Plain and ultimately in the GoM. This relationship is illustrated in the deep-water basin by (1) a high a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Hyperthermal events are evidenced by distinctive negative carbon isotope excursions (CIEs) observed globally in sedimentary records (Westerhold et al, 2020). By analogy with the Paleocene-Eocene Thermal Maximum (PETM) (Foreman et al, 2012;Chen et al, 2018;Vimpere et al, 2023) and the Middle Eocene Climate Optimum (MECO) (Peris Cabré et al, 2023), which are warming events showing increasing clastic sediment delivery to the ocean, therefore we anticipate similar sedimentary responses during the EECO. The combination of limited eustatic variability and possible high sediment supply variability creates favorable conditions to assess the role of sediment supply as a driver for stratigraphic sequences.…”
Section: Introductionmentioning
confidence: 77%
“…Hyperthermal events are evidenced by distinctive negative carbon isotope excursions (CIEs) observed globally in sedimentary records (Westerhold et al, 2020). By analogy with the Paleocene-Eocene Thermal Maximum (PETM) (Foreman et al, 2012;Chen et al, 2018;Vimpere et al, 2023) and the Middle Eocene Climate Optimum (MECO) (Peris Cabré et al, 2023), which are warming events showing increasing clastic sediment delivery to the ocean, therefore we anticipate similar sedimentary responses during the EECO. The combination of limited eustatic variability and possible high sediment supply variability creates favorable conditions to assess the role of sediment supply as a driver for stratigraphic sequences.…”
Section: Introductionmentioning
confidence: 77%
“…The prevalence of EASM enhanced seasonal precipitation and surface runoff, which can further promote the channel mobility and land plants supply . On the other hand, the enhanced coastal currents provoked by a moonsoon reduce the degradation of plant debris and are beneficial for the organic matter preservation .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of EASM enhanced seasonal precipitation and surface runoff, which can further promote the channel mobility and land plants supply. 55 On the other hand, the enhanced coastal currents provoked by a moonsoon reduce the degradation of plant debris and are beneficial for the organic matter preservation. 56 Recent research has revealed that the increasing input of terrestrial higher plants in the channels can enhance the retention of mud through baffling, stabilization, and flocculation, providing benefits for the incorporation of terrigenous organic matter into the sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, syn-PETM fan deposits are found in the Central Viking Graben east of Bressay, where they can be tied to specific wells in a relatively restricted area (Figures 11,15D). In this area, it is possible that syn-PETM fans are in fact less extensive than pre and post-PETM systems, contrasting with other areas where the PETM appears to have enhanced sediment delivery to the basin floor (Pogge von Strandman et al, 2021, Vimpere et al, 2023. This includes the Froan Basin in the Norwegian Sea, where PETM fans prograded further than before due to climate-enhanced bypass in slope-channels (Sømme et al, 2023).…”
Section: North-to-south Tilting Of the Shelf And Impacts On Lowstand ...mentioning
confidence: 96%
“…Its origin has been ascribed to different processes, including greenhouse gas release promoted by magma-sediment interaction (Svensen et al, 2004;Berndt et al, 2023) or simply large-scale, explosive LIP volcanism (Gutjahr et al, 2017;Gernon et al, 2022). Discrete paleoenvironmental modifications associated to the PETM include increased global denudation and sedimentation rates (Dunkley Jones et al, 2018;Pogge von Strandmann et al, 2021;Vimpere et al, 2023). In the Forties turbidite system in the Central Graben, a five-fold increase in sediment supply has been attributed to the PETM (Jin et al, 2022), while equivalent deposits do not appear to include similar increases in the Norwegian North Sea, in the Horda Platform (Sømme et al, 2019).…”
Section: Paleocene-eocene Thermal Maximummentioning
confidence: 99%